Digital human modeling and applications in health, safety, ergonomics and risk management : human body and motion : 10th International Conference, DHM 2019, Held as Part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings.: human body and motion : 10th International Conference, DHM 2019, Held as Part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings. Part I (2019) - Unknown
No abstract available